Impact of exercise training program attendance and physical activity participation on six minute walk distance in patients with heart failure. (2nd September 2021) - Adsett, Julie A; Morris, Norman R; Mudge, Alison M
ABSTRACT: Background : Exercise training is recommended for all people with stable heart failure (HF) however adherence is poor. This study sought to describe exercise participation in recently hospitalized HF patients who participated in a 12-week exercise training program. The association between exercise training variables and improvement in 6-min walk distance (6MWD) was also investigated. Methods : This study is a secondary analysis of results from the intervention arm of the EJECTION-HF trial (ACTRN12608000263392), (n = 140). Exercise program attendance was defined according to session frequency (< 12 sessions vs ≥ 12 sessions) and attendance duration (< 6 weeks attendance vs ≥ 6 weeks) over the 12 weeks. Physical activity at baseline and follow up were reported according to self-report of 150 min of moderate intensity exercise per week. Primary outcome was change in 6MWD at 12 weeks. Results : Being physically active (OR 3.8, CI 1.3–11.5) and frequent program attendance (OR 2.7, CI 1.2–5.9) were associated with significant improvements in 6MWD. Program duration and baseline physical activity were not significantly associated with the outcome. Conclusions : Attainment of 150 min of moderate intensity exercise per week and at least weekly attendance at the program, were associated with significant improvements in 6MWD at follow up. Efforts should be made to assist patients with HF to achieve these targets.